Globalization and Armenian Identity. Challenges and Integration (Armenia and Artsakh) - Gasparyan, Naira (Armenian Folia Anglistika, 2020)
In the present paper an effort is made to analyze the deep roots of the concerns and the past-oriented conservative Armenian attitude towards the spread of globalization. Every aspect of human life is being radically transformed due to global changes. It also helps to spread European and American values, create new values. Among the most significant changes observed as a result of globalization are said to be religious and linguo-cultural identity issues. The study of the mentioned issues is vital in an Armenian context since the people of Armenia and Artsakh, during the past 30 years of independence, have been living in an environment of undeclared war with authoritarian aggressive Azerbaijan.